Asymmetric Diplomacy and Securitization in the South China Sea - Mahroza, Jonni; Priyanto, Priyanto; Halkis, Mhd (Andalas Institute of International Studies UNAND, 2022)
Securitization in the South China Sea (SCS) invites uncertainty in the current legal and diplomatic direction. The purpose of this study is to explain that the control of economic resources by involving the military has ignored the international order. The approach method is used in phenomenological research. Primary data from various sources, researcher discussions with various experts to get a comprehensive understanding. The results show that China, based on historical rights, has failed to defend the nine-dash line (NDL) before the arbitral tribunal, but China has succeeded in shifting the issue of who has the right to control uninhabited islands in the South China Sea region into a security issue. China has occupied and developed no man's coral island. The conclusion of the researcher is that a country's strategy is not enough to look at international law, but activities that may threaten to consider building new powers. The LCS securitization conflict has led to the emergence of Asimterics Diplomacy, a strategy. The reality of Chinese activity is booming. At least it has produced; polarizing the Association of Southeast Asian Nations (ASEAN), testing the effectiveness of international law, harnessing maritime potential, and expanding national defense lines..